KILKA SPOSTRZEŻEŃ NA TEMAT PRAWA LITEWSKIEGO NA PRZEŁOMIE XVIII I XIX WIEKU W ŚWIETLE KSIĄG ZIEMSKICH SZAWELSKICH - Godek, Sławomir (Zeszyty Prawnicze, 2016)
A FEW OBSERVATIONS ON LITHUANIAN LAW AT THE TURN OF THE 18TH-19TH CENTURY FROM THE PERSPECTIVE OF THE SZAWLE (ŠIAULIAI) LEDGERS Summary Research on the legal, and especially forensic, practice in Lithuania after the dismemberment of Poland-Lithuania (1795) – an area of study embarked on only recently – should make up an important aspect of enquiry on the state of the law of Lithuania following the Partitions. In particular the aim should be to show the relationship between the former Lithuanian law and the new provisions introduced by the Partitioning Power. The specific nature of this relationship is shown by the example of the land court register (księgi ziemskie) for Szawle (Lith. Šiauliai) for 1794-1803. These records clearly show evidence of the efforts of the Russian Generals Sergei F. Golitsyn and Alexander P. Tormasov to restore the Lithuanian courts after the intermission caused by the Kościuszko Insurrection of 1794. The Russians introduced new instruments to jurisprudence including the duty to submit reports on the activities of the courts to the Russian military authorities, the use of the Julian calendar, and the issue of decisions and judgements on behalf of the Empress Catherine II. Details of these new requirements were defined in the ordinances issued by Nikolai V. Repnin, and frequently invoked. A Russian provinces act and new regulations on legal representation were also resorted to in court practice. In addition to these “foreign” elements, Šiauliai court practice shows that the old law and the 16th-century Lithuanian Statute and statutory acts passed by the Parliament of pre-partitional Poland-Lithuania still continued to be used.